The relationship between psychological abuse, athlete satisfaction, eating disorder and self-harm indicators in elite athletes - Willson, Erin; Buono, Stephanie; Kerr, Gretchen; Stirling, Ashley (Frontiers in Sports and Active Living, 2025)
IntroductionPsychological abuse continues to be the most frequently reported type of maltreatment among athletes leading to negative mental health such as low mood and self-esteem, increased anxiety, self-harm, and eating disorders. Preliminary evidence suggests athlete satisfaction can influence the perceived outcomes associated with psychological abuse. Despite its negative impacts on athletes, psychological abuse continues to be justified as a tool to enhance athletic performance.MethodsThis study sought to examine the effects of psychological abuse on athlete satisfaction and mental health indicators of eating disorders and self-harm. Participants consisted of Canadian National Team athletes who completed a survey of maltreatment in sport with items assessing psychological abuse, athlete satisfaction, eating disorder and self harm indicators (n = 794).ResultsResults indicated a negative correlation between psychological abuse and athlete satisfaction, and a positive correlation with eating disorders and self-harm indicators. Additionally, athlete satisfaction was a significant moderator of psychological abuse on eating disorder and self-harm indicators. High athlete satisfaction buffered against the negative effects of psychological abuse on self-harming indicators in non-aesthetic and weight based sport and non-team sport athletes. Conversely, the interaction between athlete satisfaction and psychological abuse was marginally significant in predicting increased negative effects on eating disorders in aesthetic and weight based sport athletes.DiscussionThese findings highlight the detrimental effects psychological abuse can have on athletes in relation to eating disorders and self-harm, and the buffering role of athlete satisfaction on self-harm but not eating disorder indicators in aesthetic and weight based sport athletes. Recommendations include increased attention to preventing psychological abuse in sport.